Unsupervised Exercise and Mobility Loss in Peripheral Artery Disease: A Randomized Controlled Trial. Issue 5 (May 2015) - McDermott, Mary M.; Guralnik, Jack M.; Criqui, Michael H.; Ferrucci, Luigi; Liu, Kiang; Spring, Bonnie; Tian, Lu; Domanchuk, Kathryn; Kibbe, Melina; Zhao, Lihui; Lloyd Jones, Donald; Liao, Yihua; et al.
Abstract : Background: Few medical therapies improve lower extremity functioning in people with lower extremity peripheral artery disease (PAD). Among people with PAD, we studied whether a group‐mediated cognitive behavioral intervention promoting home‐based unsupervised exercise prevented mobility loss and improved functional performance compared to control. Methods and Results: One hundred ninety‐four PAD participants were randomized. During months 1 to 6, the intervention group met weekly with other PAD participants and a facilitator. Group support and self‐regulatory skills were used to help participants adhere to walking exercise. Ninety‐percent of exercise was conducted at or near home. The control group attended weekly lectures. During months 6 to 12, each group received telephone contact only. Primary outcomes have been reported. Here we compare changes in exploratory outcomes of mobility loss (the inability to climb a flight of stairs or walk one‐quarter mile without assistance), walking velocity, and the Short Physical Performance Battery. Compared to controls, fewer participants randomized to the intervention experienced mobility loss at 6‐month follow‐up: 6.3% versus 26.5%, P =0.002, odds ratio=0.19 (95% CI=0.06 to 0.58) and at 12‐month follow‐up: 5.2% versus 18.5%, P =0.029, odds ratio=0.24 (95% CI=0.06 to 0.97). The intervention improved fast‐paced 4‐m walking velocity at 6‐month follow‐up ( P =0.005) and the Short Physical Performance Battery at 12‐month follow‐up ( P =0.027), compared to controls. Conclusions: In exploratory analyses, a group‐mediated cognitive behavioral intervention promoting unsupervised walking exercise prevented mobility loss and improved functioning at 6‐ and 12‐month follow‐up in PAD patients. Clinical Trial Registration: URL:http://clinicaltrials.gov . Unique identifier: NCT00693940.